Australia and New Zealand Islets and Pancreas Transplant Registry Annual Report 2018—Pancreas Waiting List, Recipients, and Donors. Issue 10 (October 2018) - Webster, Angela C.; Hedley, James; Robertson, Paul; Mulley, William R.; Pilmore, Helen L.; Pleass, Henry; Kelly, Patrick J.
Abstract : Background: This is a synopsis of the registry report from the Australia and New Zealand islet and pancreas transplant registry. The full report is available athttp://anziptr.org/reports/ . Methods: We report data for all solid organ pancreas transplant activity from inception in 1984 to end 2017. Islet-cell transplantation activity is reported elsewhere. Data analysis was performed using Stata software version 14 (StataCorp, College Station, TX). Results: From 1984 to 2017 a total of 809 solid organ pancreas transplants have been performed in Australia and New Zealand, in 790 individuals. In 2017, 52 people received a pancreas transplant. By center, this was; Auckland (4), Monash (17), and Westmead (31). In 2017, 51 transplants were simultaneous pancreas kidney, whereas 1 was pancreas after kidney, and none were pancreas transplant alone. Conclusions: The number of pancreas transplants performed in Australia and New Zealand was slightly lower in 2017 but continues to increase over time.